Analisis Perbedaan Implementasi Buku Pembelajaran dalam Kurikulum 2013 dan Kurikulum Merdeka di Sekolah Dasar - Luki Eka Ferdian; Hafidz Pradita; Avivvah Sulistyowati; Gressia Fani Ekawati; Bayu Purbha Sakti (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
The shift in curriculum policy from the 2013 Curriculum (K-13) to the Merdeka Curriculum (KM) demands comprehensive adjustments to learning materials, particularly textbooks, which serve as primary pedagogical guides. However, a systematic comparative study of textbooks from both curricula at the elementary school (SD) level remains limited. This study aims to analyze the differences in textbook implementation between the 2013 Curriculum and the Merdeka Curriculum at the elementary school level. This study employed a library research method with a descriptive qualitative approach. Data were collected through systematic document analysis of official curriculum documents, textbooks for grades I–VI, and related ministerial regulations, supplemented by peer-reviewed journal articles (2013–2024). Content analysis and comparative analysis techniques were applied following the Miles, Huberman, and Saldaña (2014) framework, with source triangulation ensuring data validity. The findings reveal significant differences in textbook structure, pedagogical approach, competency orientation, and flexibility of use. K-13 textbooks adopt a thematic integrative structure with a structured scientific approach, while Merdeka Curriculum books prioritize essential content, project-based learning, differentiated instruction, and reinforcement of the Pancasila Student Profile (Profil Pelajar Pancasila). The Merdeka Curriculum promotes greater pedagogical autonomy for teachers and deeper conceptual understanding for students. These findings contribute insights for educators, curriculum developers, and policymakers in designing effective curriculum transition strategies.